Kardiomiopatia rozstrzeniowa i przerostowa u płodu matki z cukrzycą ciężarnych - opis przypadku - Monika Kwiatek; Jerzy Węgrzynowski; Grażyna Dawid; Anita Horodnicka-Józwa; Elżbieta Petriczko; Agnieszka Biczysko-Mokosa (Pediatric Endocrinology, Diabetes and Metabolism)
There is an increased risk of a hypertrophic cardiomyopathy and congenital heart defects among newborns of diabetic mothers. We report a case of hypertrophic cardiomyopathy preceded with dilated cardiomyopathy in a fetus of a diabetic mother. The fetal echocardiography at the 23rd week of gestation revealed signs of dilated cardiomyopathy with signs of cardiac failure. Under the echocardiographic monitoring the successful treatment was performed. In spite of poor prognosis, the child was born at the 39th gestation week in a good condition.